The effect of substrate selection on the cultivation of edible mushrooms - Gueffaf, Mohamed Amine; Touati-Hattab, Siham; Benkattas, Wassila (Laghouat : Université Amar Telidji - Département d'agronomie, 2025)
Mushrooms have been valued for centuries for their nutritional and medicinal properties. Rich in proteins, vitamins (B and D), minerals (selenium, potassium), dietary fiber, and bioactive compounds (polysaccharides, phenolics, terpenoids), they possess antioxidant, anti- inflammatory, immunomodulatory, and anticancer effects. In this study, we cultivated three mushroom species: a strain of the Pleurotus ostreatus genus and its propagation on cellulosic substrates, a strain of Agaricus bisporus, and Terfezia (desert truffle). The mycelium of each species was obtained after cultivation on a PDA and SDA. The results show that growth was better on PDA (good development) for Pleurotus and Agaricus, while Terfezia exhibited weak radial growth. The inoculum preparation for Pleurotus was carried out on three cereal grain- based substrates (wheat, barley, and corn), while only wheat was used as a substrate for Agaricus. For Terfezia, the inoculum was produced in a honey-based liquid medium as well as another solid medium that we prefer to keep anonymous. The results were remarkable, with good mycelial dispersion on the grains and other substrates. Pleurotus ostreatus was cultivated on wheat straw took almost 42 days and coffee grounds almost 32 days, while Agaricus bisporus required a specific growth medium. Pleurotus yielded a good harvest on the coffee grounds fruiting substrate compared to the other substrates selected in this study.